Upah Penggilingan Padi Di Desa Pangkat Kecamatan Lembah Sorik Marapi Kabupaten Mandailing Natal Dalam Kajian Al ‘Urf - Siregar, Resi; Hamdanil; Siti Hawa (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2024)
In Islamic law, it has been stipulated that a contract is considered valid if it is carried out by mukallaf and there must be clarity from the side of the contract and known by both parties so that no one is harmed. This research is a descriptive field research, the analysis of data sources comes from field research. The sample of this study is rice mill owners, rice mill employees and the community that grinds rice, data collection is used by observation, interview and documentation methods at the research site. Data processing is carried out using data editing and systematization techniques. The results of the research in taking wages for rice milling in Prank Village, Sorik Marapi Valley District use a payment system using rice and this has become a habit. In the billing of wages, sacks are taken as many as 6 muk/sacks, and the practice of wages is carried out by following the customs and customs carried out in Prank village, Sorik Marapi Valley, Mandailing Natal Regency, have met the requirements and are in harmony in wages. However, it would be better if it fulfilled the provisions of the principles in the contract, including the absence of an agreement on wage collection and non-transparency of rice milling services, unilateral wage determination that was not witnessed between the service user and the service owner.